Speed Control Analysis of Frequency Changes in Three Phase Synchronous Motor with Variable Speed Drive (VSD) - Lasmana Lasmana; Muhammad Aziz Musyaffa; Taryo Taryo (Institut Teknologi Dirgantara Adisutjipto, 2025)
This study investigates the impact of frequency adjustment using a Variable Speed Drive (VSD) on the performance of a three-phase AC synchronous motor under both no-load and load conditions. Energy inefficiency in industrial systems often results from mismatches between motor speed and load demands. The motor was tested at frequencies ranging from 20 Hz to 50 Hz to evaluate changes in speed, input power, torque, and efficiency. Unlike previous studies that focused solely on motor speed, this research provides a more comprehensive performance analysis. The results show that increasing frequency leads to higher motor speed and power consumption, but a decrease in torque. Under no-load conditions, speed increased from 607 RPM at 20 Hz to 1506 RPM at 50 Hz, while torque dropped from 1.57 Nm to 0.63 Nm. Under load, speed increased from 88 RPM to 683 RPM, and torque declined from 10.9 Nm to 1.39 Nm. Although motor efficiency decreases at higher frequencies due to increased magnetizing current caused by the constant V/f ratio, it must be emphasized that VSDs can significantly enhance energy efficiency by allowing the motor to operate at an optimal speed according to the load, instead of continuously running at full speed. Therefore, dynamic frequency control based on load variation is essential to optimize motor performance. VSDs thus play a vital role in intelligent control strategies aimed at improving energy efficiency in industrial applications.